1998
DOI: 10.1063/1.122378
|View full text |Cite|
|
Sign up to set email alerts
|

Structural and magneto-transport properties of electrodeposited bismuth nanowires

Abstract: Arrays of semimetallic Bi nanowires have been successfully fabricated by electrodeposition. Each nanowire consists of elongated Bi grains along the wire direction. Very large positive magnetoresistance of 300% at low temperatures and 70% at room temperature with quasilinear field dependence has been observed. These features are desirable for wide-range field sensing applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
111
0
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 198 publications
(115 citation statements)
references
References 21 publications
3
111
0
1
Order By: Relevance
“…22,21 The as-deposited Bi films, 1-20 m thick, are polycrystalline but with very large grains, whose sizes are comparable to the film thickness. This fact alone is a marked improvement over traditional thin film fabrication methods.…”
Section: Fabrication and Structural Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…22,21 The as-deposited Bi films, 1-20 m thick, are polycrystalline but with very large grains, whose sizes are comparable to the film thickness. This fact alone is a marked improvement over traditional thin film fabrication methods.…”
Section: Fabrication and Structural Characterizationmentioning
confidence: 99%
“…Recently, during the course of our exploration of the fabrication of Bi nanowire arrays into nanoporous templates, 22,23 in which electrodeposition is the only viable method, we have found electrodeposition to be a superior deposition method for fabricating high quality Bi thin films. 20,21 After further processing, these electrodeposited films become single-crystals Bi thin films, in which we have observed enormous MR effects of as much as 400 000% at low temperatures and 300% at room temperature, and pronounced Shubnikov-de Haas ͑S-dH͒ oscillations.…”
Section: Introductionmentioning
confidence: 99%
“…6 This method has enabled us to obtain Bi nanowires with large grains. 7 In this paper, we report the first magnetoresistance measurements of electrodeposited Bi nanowires under very high magnetic fields up to Bϭ55 T.…”
mentioning
confidence: 99%
“…Transmission electron microscopy ͑TEM͒ and electron diffraction have shown that the wires are polycrystalline, with grain sizes up to ϳ2 -4 times the pore diameters with no preferred orientation. 7 Electrical contacts were made on both sides of the membranes with vacuum-deposited Au layers and silver epoxy. The temperature dependence of the resistance at zero field was measured at Tϭ4.2Ϫ290 K. High-field magnetoresistance was measured in fields up to Bϭ55 T using a pulsed magnet at various temperatures between Tϭ4.2 K and 290 K in both longitudinal (B ʈ wires) and transverse (B Ќ wires) orientations.…”
mentioning
confidence: 99%
“…It is remarkable that even for nanowires built up by large grains the specific electrical resistivity is about threefold the bulk value. Different groups reported measurements of the resistance of bismuth nanowires as a function of temperature, revealing different behaviours Liu et al, 1998;Zhang et al, 2000). For nanowire arrays prepared by high-pressure injection in alumina templates and for single wires electrochemically deposited in singlepore ion track-etched membranes with d > 200 nm a non-monotonic resistance versus temperature behaviour was reported.…”
Section: Finite-size Effectsmentioning
confidence: 99%